A nation‐wide study on the common reasons for infant formula supplementation among healthy, term, breastfed infants in US hospitals. Issue 2 (14th December 2021) - Bookhart, Larelle H.; Anstey, Erica H.; Kramer, Michael R.; Perrine, Cria G.; Reis‐Reilly, Harumi; Ramakrishnan, Usha; Young, Melissa F.
Abstract: In‐hospital infant formula supplementation of breastfed infants reduces breastfeeding duration, yet little is known about common reasons for infant formula supplementation. We examined the three most common reasons for in‐hospital infant formula supplementation of healthy, term, breastfed infants in the US reported by hospital staff. Hospital data were obtained from the 2018 Maternity Practices in Infant Nutrition and Care survey ( n  = 2045), which is completed by hospital staff. An open‐ended question on the top three reasons for in‐hospital infant formula supplementation was analyzed using thematic qualitative analysis and the frequencies for each reason were reported. The top three most common reasons for in‐hospital infant formula supplementation reported by hospital staff included medical indications (70.0%); maternal request/preference/feelings (55.9%); lactation management‐related issues (51.3%); physical but non‐medically indicated reasons (36.1%); social influences (18.8%); perceived cultural/societal/demographic factors (8.2%) and medical staff/institutional practices (4.7%). These findings suggest that a variety of factors should be considered to address unnecessary infant formula supplementation. Lactation management support delivered in a timely and culturally sensitive manner and targeted to mother‐infant dyads with potential medical and physical indications may reduce unnecessary in‐hospital infant formula supplementation. Key messages: The three most commonly reported reasons by hospital staff for infant formula supplementation were found to be related to medical indications (70.0%); maternal request/preference/feelings about breastfeeding such as frustration or lack of confidence (55.9%); lactation management‐related issues (51.3%); physical but non‐medically indicated reasons (36.1%); social influences (18.8%); perceived cultural/societal/demographic factors (8.2%); and medical staff/institutional practices (4.7%). Underlying many of the reported three most common reasons for infant formula supplementation is potentially lack of lactation management support that considers the social influences (e.g. from family and friends) and that is culturally relevant. These findings suggest that a variety of factors should be considered to address unnecessary infant formula supplementation.